Optimizing Scour Protection in Downstream Stilling Basins: Insights from USBR-Type Weirs - Abdurrosyid, Jaji; Wibowo, Gurawan Jati (Engineering Research: Perspectives on Recent Advances Vol. 5, 2025)
In the downstream part of the weir, especially in the stilling basin, there is a hydraulic jump phenomenon caused by the change in flow from supercritical flow to subcritical flow. The hydraulic jump in the stilling basin of the weir causes bottom scouring, especially in the unprotected downstream part of the weir. This can result in significant damage to the overall structure of the weir. So that this downstream part requires protection to overcome scouring. Therefore, to overcome this problem, a laboratory study is needed on scouring and its mitigation in the downstream part of the weir. This research was conducted at the Hydraulics Laboratory of the Surakarta River Research Center using a recirculation channel. The dimensions of the recirculation channel are: length = 24 m; width = 0.49 m; and height = 0.60 m. The basic material of the recirculation channel is fine sand (sieve diameter = 2 mm) with a thickness of 0.20 m layered along the channel. The channel slope is 0.004, and it is assumed that there is no sediment load in the upstream part of the weir. This study uses a USBR (United States Bureau of Reclamation) type weir model consisting of USBR-I, USBR-II, USBR-III, and USBR-IV types. The model is placed approximately ± 9.0 m from the upstream with the aim of not being affected by wave ripples from the Inlet. The experiment was conducted using 4 variations of running discharge and 3 variations of running protection. The results showed that the maximum scour depends on the flow velocity, shear velocity, and flow height downstream of the stilling basin. In addition, the maximum scour is also affected by the Reynolds number and gravity (as the Froude number). These parameters are significantly interdependent. Furthermore, there is a significant reduction in scour downstream of the stilling basin protected by Rip-rap (RR) ¼ Lmax, RR ½ Lmax, and RR Lmax. In addition, protection using rip-rap length Lmax or loose gravel can protect scour with the smallest scour depth. However, scour still occurs downstream of the stilling basin even though there is protection along Lmax. Scouring depth reduction (Ym Reduction) on Rip-rap installation = Lmax RR with the largest reduction is USBR-IV type 92.94%, and the smallest is USBR-II type 81.21%. While the largest reduction in Scouring Length (Lm Reduction) is USBR-IV type 75.55%, and the smallest is USBR-I type 47.32%. So overall, the maximum Scouring Depth reduction (Ym Reduction) occurs in USBR-IV type, and the smallest in USBR-II type. While the maximum Scouring Length reduction (Lm Reduction) occurs in USBR-IV type, and the smallest in USBR-I type.